The Effect of Capital Budgeting Decisions on Profitability: Selected Companies from Developed and Developing Countries - Alawamleh, Yaser M. A. K. (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi(DAÜ), 2021)
The purpose of this study is to determine the impact of capital budgeting decisions on the profitability of listed companies in Germany, Canada, Jordan, and Egypt. Study population is 64 listed companies. The main independent variable is capital expenditure as measured by natural logarithm of fixed assets. In addition to this variable, study has leverage, liquidity and age of the company as control variables. As for dependent variable, profitability is used measured by return on assets. Secondary data was collected for a period of 9 years on an annual basis. The study employed a descriptive panel data analysis with OLS regression and random regression as robustness to analyze the association between the variables. Eviews 10 was used for analyzing the secondary data. ANOVA results show that the F statistic was significant at 5% level with a p=0.000. Therefore, the model was fit to explain the relationship between the selected variables. The study finds that capital expenditure affects financial performance significantly and positively in both developed and developing countries. In addition to this, control variables are also found to be significant and have signs as expected. However, the study also finds that, the magnitude of the impact of capital expenditure on performance is higher in developed countries relative to developing countries. This relatively lower impact may be explained by the fact that firms in developing economies have not adapted proper and effective project appraisal means for capital budgeting decision making. Based on the findings, the study puts forward some recommendations. Keywords: Capital Budgeting, Profitability, Capital Expenditure

ÖZ: Bu çalışmanın amacı, sermaye bütçeleme kararlarının Almanya, Kanada, Ürdün ve Mısır'daki şirketlerin karlılığı üzerindeki etkisini belirlemek ve ölçmektir. Çalışmada borsada işlem gören 64 şirket incelenmiştir. Ana bağımsız değişken, sabit varlıklara yapılan harcamalarıdır. Bu değişkenler yanında çalışmanın kontrol değişkenleri olarak kaldıraç, likidite ve şirketin yaşı yer almaktadır. Bağımlı değişken için ise karlılığı gösteren varlık getirisi kullanılmıştır. İkincil veriler, 9 yıllık bir dönem için toplanmıştır. Analiz için tanımlayıcı veri analizi kullandı. Çalışmada, tanımlayıcı istatistikler analizi yanında, değişkenler arasındaki ilişkiyi analiz etmek için OLS regresyonu ve sağlamlık testi olarak rastgele regresyon kullanılmıştır. Verileri analiz etmek için Eviews kullanılmıştır. Anova testleri, F istatistiğinin% 5 düzeyinde p = 0.000 ile anlamlı olduğunu göstermektedir. Bu nedenle model, seçilen değişkenler arasındaki ilişkiyi açıklamaya uygundur. Çalışma, sermaye harcamalarının hem gelişmiş hem de gelişmekte olan ülkelerde finansal performansı önemli ve olumlu etkilediğini ortaya koymaktadır. Buna ek olarak, kontrol değişkenlerinin de anlamlı olduğu ve beklenen işaretlere sahip olduğu bulunmuştur. Bununla birlikte, çalışma aynı zamanda sermaye harcamalarının karlılık üzerindeki etkisi büyüklüğünün gelişmekte olan lkelerde gelişmiş olan ülkelere göre daha düşük olduğunu ortaya koymaktadır. Bu görece daha düşük etki, gelişmekte olan ekonomilerdeki firmaların sermaye bütçeleme kararları için uygun ve etkili proje değerlendirme araçlarını uyarlamamış olmasıyla açıklanabilir. Bulgulara dayanarak çalışma bazı öneriler ortaya koymuştur. Anahtar Kelimeler: Sermaye Bütçelemesi, Karlılık, Sabit Sermaye Harcaması
Master of Science in Banking and Finance. Institute of Graduate Studies and Research. Thesis (M.S.) - Eastern Mediterranean University, Faculty of Business and Economics, Dept. of Banking and Finance, 2021. Supervisor: Prof. Dr. Mustafa Besim.
Keywords: Banking and Finance; Capital Budgeting; Profitability; Capital Expenditure